2004
DOI: 10.1128/aem.70.9.5331-5335.2004
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and Infectious Dose ofEscherichia coliO157:H7 in Swine

Abstract: Escherichia coli O157:H7 is only occasionally isolated from healthy swine, but some experimentally infected animals will shed the organism in their feces for at least 2 months. Potential explanations for the paucity of naturally occurring infections in swine, as compared to cattle, include a lack of animal-to-animal transmission so that the organism cannot be maintained within a herd, a high infectious dose, or herd management practices that prevent the maintenance of the organism in the gastrointestinal tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 33 publications
3
50
0
1
Order By: Relevance
“…coli O157:H7 in wild pig and cattle feces. E. coli O157:H7 infection and shedding occur frequently among cattle and pigs (19,20,22,27 precipitation of 59.1 mm. Summer and early fall months (June to September) were relatively dry, with the minimum average monthly precipitation occurring in July (0.1 mm).…”
Section: Methodsmentioning
confidence: 99%
“…coli O157:H7 in wild pig and cattle feces. E. coli O157:H7 infection and shedding occur frequently among cattle and pigs (19,20,22,27 precipitation of 59.1 mm. Summer and early fall months (June to September) were relatively dry, with the minimum average monthly precipitation occurring in July (0.1 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Cattle are considered to be the major reservoir of E. coli O157:H7 (Baker et al, 2007;Wang et al, 2008;Williams et al, 2008). Recent studies have also demonstrated that, conventional pigs were permissive host for E. coli O157:H7 (Booher et al, 2002;Cornick and Helgerson, 2004), though the prevalence of the organism in these studies was generally low, except for the results from Chile and Chinese Mainland and both suggested that, pig might be an important source of this organism in some countries (Borie et al, 1997;Zheng et al, 2005). Also, one family outbreak had been specifically traced back to pork salami and the E. coli O157 isolates from the couple and the salami carried stx 1 , stx 2 and eae genes and shared the same PFGE pattern (Conedera et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large outbreak of human cases in the United States was linked to spinach potentially contaminated by both feral swine and cattle manure (12). E. coli O157:H7 can be carried by experimentally infected swine for at least 2 months (3, 4), and we have shown that transmission between naïve animals penned with an infected donor occurs freely (3,4,8). The objective of the current study was to determine whether or not E. coli O157:H7 could be transmitted to naïve animals that did not have any direct contact with an infected donor animal.…”
mentioning
confidence: 99%
“…The inoculum strain used depended on the antibiotic resistance of the background commensal flora. Previously we have shown that there are no significant differences between these strains in colonization of pigs and sheep (7,8). Three days after inoculation the donor animal was moved in with the naïve animals and placed in pen 1 (Fig.…”
mentioning
confidence: 99%